Upaya Perubahan Perilaku Dalam Pencegahan Stunting - Cerah Puspinarti; Misnaniarti Misnaniarti; Elvi Sunarsih (Jurnal Ners, 2023)
Stunting has become a global health phenomenon that occurs in several countries around the world. The problem of stunted linear growth during the first 1,000 days of an infant's life has garnered much attention. Many studies have been conducted to eliminate the high prevalence of stunting. The government has decided to overcome this infant health problem by appointing several target. The National Strategy Plans to Accelerate Stunting Prevention have been carried out by prioritising the interventions of sensitive nutrition. Some interventions are being worked on including behaviour change. This intervention is in line with the 5 pillars of stunting prevention: the national campaign and change of behaviour. The behaviour change will be carried out deeply to discover some reasons that motivate the change of behaviour, clean water and latrines sanitation, exclusive breastfeeding, food parenting, health workers, posyandu cadres and stake holders. Behaviour change in a community will encounter many obstacles due to economic, traditional and sociocultural differences. This implicity means that the role of posyandu cadres among the communities is needed. Improving the function and activeness of posyandu cadres is an urgent step that must be taken immediately. Because no matter how many health workers are deployed in the field, they will not be able to get rid of the role of posyandu cadres who daily deal directly with the community and live in it and understand the sociocultural ins and outs of the community in their area of responsibility. Posyandu cadres are also part of an activity that includes many things that affect their performance and activity. The following article is a systematic review to look for behaviour change efforts that should be carried out immediately in the prevention of stunting.